2019
DOI: 10.26434/chemrxiv.7629680.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Derivatisation of Parthenolide to Address Chemoresistant Chronic Lymphocytic Leukaemia

Abstract: A protocol for growing, extracting and derivatising parthenolide obtained from feverfew varieties is reported. Aminated parthenolide derivatives were prepared via 1,4-addition of primary or secondary amines utilising established and modified methods. The parthenolide derivatives’ drug-likeness properties were computed and they were screened for anti-leukaemic activity against the TP53-mutant, chemo-refractory, MEC1 chronic lymphocytic leukaemia (CLL) cell line. A screening cascade identified a small number of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Inspired by the work of Neelakantan et al . in identifying compound 2a as a promising NF-κB inhibitor [ 28 ], the co-authors of this report had previously identified compound 2b as a potential anti-CLL therapy [ 8 , 9 ], which showed improved drug metabolism and pharmacokinetics (DMPK) properties. To the best of our knowledge the anti-leukaemic activity of aniline-derivatisation on parthenolide has not previously been addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the work of Neelakantan et al . in identifying compound 2a as a promising NF-κB inhibitor [ 28 ], the co-authors of this report had previously identified compound 2b as a potential anti-CLL therapy [ 8 , 9 ], which showed improved drug metabolism and pharmacokinetics (DMPK) properties. To the best of our knowledge the anti-leukaemic activity of aniline-derivatisation on parthenolide has not previously been addressed.…”
Section: Resultsmentioning
confidence: 99%
“…Parthenolide ( 1 ) is a natural product readily extracted from varieties of the plant feverfew (Tanacetum parthenium) [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ] and has been widely reported to display promising activity against various diseases including types of cancer [ [16] , [17] , [18] , [19] , [20] , [21] ]. Mechanistically, parthenolide targets leukaemia cells by depleting glutathione and by alkylating Cys38 of NF-kB to inhibit DNA-binding [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…77 The other gene enrichment pathways, such as RNA degradation, P53 signaling pathway and cell cycle, were also observed associated with genomic instability. [78][79][80] Additionally, the GILncSig is strongly associated with the phenotype of the tumor mutator and the UBQLN4 expression level in LUAD, both of which are essential markers of genomic instability. Moreover, three external GEO data sets showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [218], obtained a novel parthenolide derivative, HMPPPT, a 13-substituted derivative ((3R,3aS,9aR,10aR,10bS,E)-3-((4-(6-hydroxy-2-methylpyrimidin-4-yl)piperidin-1-yl)methyl)-6,9a-dimethyl-3a,4,5,8,9,9a,10a,10b-octahydrooxireno [2 ,3 :9,10]cyclodeca[1,2-b]furan-2(3H)-one) (12) (Figure 9), with better bioavailability and pharmacological properties than DMAPT. In vitro studies pointed to compound 12 as the most promising derivative, from safety profile and ADME property standpoints.…”
Section: Parthenolidementioning
confidence: 99%
“…The newly identified compound was shown to have pro-oxidant activity and in silico molecular docking studies with components of the NF-κB pathway also supporting a pro-drug mode of action. This mechanism included release of parthenolide and covalent interaction with one or more proteins involved in that pathway [218]. The in vivo oral bioavailability study of compound 12 in murine PK at 10 mg/kg indicated that it has advantageous pharmacological properties and therefore can be considered an agent to be considered in therapy against drug resistant chronic lymphocytic leukemia [218].…”
Section: Parthenolidementioning
confidence: 99%